On the Problem of Rationality of Economic Choice in the Context of Psychological Factors - Voskanyan, Karlen (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
The problem of economic choice and its rationality has now become the subject of research in social sciences. An economic choice is considered rational, as a result of which, by making certain expenses, a person satisfies his needs to the maximum extent. Limited resources force a person to use financial resources sparingly to satisfy as many needs as possible. The classical economic approach assumes that when making economic choices a person is not influenced by others because the needs and preferences which are determined by individual psychophysiological features, are mostly stable. Currently, there are three main trends in economic theory: neoclassical, institutional and evolutionary which are based on the principles of absolute or limited rationality of economic behavior. In this article by the term “rational economic choice” we mean the choice that best meets a person’s expectations and in which case the expected utility function takes on a maximum value. By the utility function, economists mean the functions expressing the dependence of the amount of goods and services used by the economic subject in a given period and the costs incurred by him. The utility function expresses the relationships between the person’s preferences and actions aimed at satisfying needs. Preferences and actions in the article are considered in the context of psychological factors. The article presents a number of approaches related to the rationality of economic choice. The problem of rationality is considered with the help of a utility function given on the commodity-money space . We proceeded with the economic principle that no matter what factors determine the economic behavior of a person, the solution to the problem of satisfying his material and spiritual needs will ultimately lead to the problem of cost reduction. We determined the effectiveness of the sample not only by the amount of financial expenses incurred by the realization of the selection, but also by the preference given to the sample, which is a psychophysiological feature of the person.